Use of arteriovenous fistula in peritoneal dialysis in France (RDPLF data - Christian Verger; Emmanuel Fabre (RDPLF, 2021)
There is a consensus not to systematically create arteriovenous fistula (AVF) in patients treated with peritoneal dialysis. We wanted to verify in the French Language Peritoneal Dialysis Register (RDPLF) database what the practices are in France. We selected patients who stopped peritoneal dialysis between December 2016 and December 2021 and who, before their peritoneal dialysis treatment, had not been treated with hemodialysis or transplant before. Only 5.2% of patients had an AVF during PD, and 86.7% of these did not use it. Of the patients who did not have AVF, however, 38% were transferred to hemodialysis, often with a central venous catheter. While it is probably important to have a predictive algorithm to avoid definitive transfers in hemodialysis with a central venous catheter when this transfer can be planned, this report confirms the pointlessness of creating a systematic vascular access in PD, particularly when there is a kidney transplant project.